AN ANALYSIS OF HOUSING POLICY EFFECTIVENESS IN INDONESIA THROUGH COMPARISON BETWEEN DEVELOPED AND DEVELOPING COUNTRIES’ HOUSING POLICY (Journal of International Studies, 2025)
This study examines Indonesia's challenges in meeting its citizens' housing needs amidst globalisation and economic liberalisation. The research aims to identify effective housing policies from developed and developing countries that can be adapted to the Indonesian context. Through a comparative analysis of housing policies in North Western Europe, the United States, Thailand, the Philippines, and Malaysia, the study explores different approaches to addressing housing affordability and accessibility. Findings reveal that developed countries leverage robust institutions and capital resources to implement tax and subsidy mechanisms, while developing countries face limitations due to financial constraints and low tax revenues. The study suggests that Indonesia can adopt successful policies from developed nations, such as targeted subsidies and incentivising private sector participation, while tailoring them to align with Indonesian values and socioeconomic conditions. This study examines Indonesia's challenges in meeting its citizens' housing needs amidst globalisation and economic liberalisation. The research aims to identify effective housing policies from developed and developing countries that can be adapted to the Indonesian context. Through a comparative analysis of housing policies in North Western Europe, the United States, Thailand, the Philippines, and Malaysia, the study explores different approaches to addressing housing affordability and accessibility. Findings reveal that developed countries leverage robust institutions and capital resources to implement tax and subsidy mechanisms, while developing countries face limitations due to financial constraints and low tax revenues. The study suggests that Indonesia can adopt successful policies from developed nations, such as targeted subsidies and incentivising private sector participation, while tailoring them to align with Indonesian values and socioeconomic conditions. This study reveals key differences in how developed and developing countries approach housing policy. While developed nations leverage strong institutions and significant capital for tax and subsidy programs to improve affordability and access, developing countries like Indonesia face limitations due to financial constraints and lower tax revenues. The research contributes valuable comparative analysis and policy recommendations for Indonesia, suggesting the adoption of targeted subsidies and incentivising private sector participation tailored to the country's unique context. Ultimately, it highlights the need for context-specific solutions to address housing challenges in a globalised world.